1994
DOI: 10.1016/0270-9139(94)90073-6
|View full text |Cite
|
Sign up to set email alerts
|

Small-for-size liver transplanted into larger recipient: A model of hepatic regeneration

Abstract: Orthotopic liver transplantation was performed in 60 recipient rats weighing 200 to 250 gm. Sixty rats of the same strain were used as liver donors, 30 weighing 100 to 140 gm (small for size) and the other 30 weighing 200 to 250 gm (same size). Mter 1, 2, 3, 4, 7 and 14 days (n = 5 each) DNA synthesis, nuclear thymidine labeling and mitoses were increased in both the smallfor-size and same-size groups, but significantly more in the former. These changes were maximal after 48 to 72 hr, similar to but later than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The liver is the only organ that responds to a loss of functional tissue by a process of compensatory growth, also called ‘ regeneration’ , to reach a volume sufficient to meet the physiological requirements of the organism . Liver regeneration allows the liver to recover from toxic or viral injuries but also allows performance of partial hepatectomy and partial liver transplantation .…”
Section: Introductionmentioning
confidence: 99%
“…The liver is the only organ that responds to a loss of functional tissue by a process of compensatory growth, also called ‘ regeneration’ , to reach a volume sufficient to meet the physiological requirements of the organism . Liver regeneration allows the liver to recover from toxic or viral injuries but also allows performance of partial hepatectomy and partial liver transplantation .…”
Section: Introductionmentioning
confidence: 99%
“…Except in pediatric recipients, these grafts are typically significantly smaller than a calculated standard liver volume, with a minimal volume of liver mass necessary for successful recovery (1–3). Both animal studies and clinical experience have demonstrated decreased function and poor survival of grafts that do not make these minimal requirements, a condition termed ‘small‐for‐size’, manifested by prolonged cholestasis and appearance of significant ischemic‐type injury on pathologic review (4,5). However, the mechanisms of this type of injury, the reasons for graft failure and particularly the ability of the partial liver graft to regenerate after transplantation are not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…A reduced GRWR in rat OLT can be achieved by two methods: (1) using body weight (BW)-mismatched donor and recipient animals [49] or (2) via reducing the graft size by liver resection [37]. Zhong and colleagues [35,50,51,52] have repeatedly reported on the model of 25% small-for-size liver transplantation using BW-mismatched animals.…”
Section: Technical Issues Concerning P-olt In Ratsmentioning
confidence: 99%
“…Besides transplantation models, numerous experimental approaches are known and used to investigate the phenomenon and mechanisms of transplantation injury [110], small-for-size syndrome [49,60], immunology/rejection [111], cold/warm ischemia-reperfusion [110,112,113], and regeneration of the liver [60,114]. …”
Section: Place Of Rat Olt and P-olt Models In Transplantation Researchmentioning
confidence: 99%